Structural diversification of the aminobicyclo[4.3.0]nonane skeleton using alkynylsilyl-derived allylic trichloroacetimidates. Issue 14 (17th March 2017) - Mostafa, Mohamed A. B.; McMillan, Angus E.; Sutherland, Andrew
Abstract : The late-stage synthesis of aminobicyclo[4.3.0]nonane analogues has been achieved from a key vinylsilane intermediate, prepared in turn by a one-pot multi-step process using an alkynylsilyl-derived allylic trichloroacetimidate. Abstract : The amino substituted bicyclo[4.3.0]nonane is a molecular scaffold found in a wide range of natural products and medicinal agents. Despite this, synthetic methods for the general preparation of this structural motif are sparse. Here we evaluate a diastereoselective approach for the preparation of vinylsilyl derived aminobicyclo[4.3.0]nonanes using a one-pot multi-bond forming process involving a Pd(ii )-catalysed Overman rearrangement, a Ru(ii )-catalysed ring closing enyne metathesis reaction, followed by a hydrogen bonding directed Diels–Alder reaction. We show that a benzyldimethylsilyl-substituted alkene analogue is amenable to further functionalisation and the late stage generation of diverse sp 3 -rich, drug-like aminobicyclo[4.3.0]nonane scaffolds with up to six stereogenic centres.